Pengurangan Porosity Pada Dies Akibat Pressure Rendah - Wiyatno, Tri Ngudi; Anggara, M. Hatta Ari; Nugraha, Rifal; Krismanto, Rendi; Aqbar, Ikbal (DPPM UNIVERSITAS PELITA BANGSA, 2021)
Total Productive Maintenance is one of the maintenance process methods developed to increase productivity in the work area, by making the process more reliable and less wasteful. This method is part of Lean Manufacturing. A common problem in TPM is due to the lack of comprehensive involvement of production operators in machine maintenance and the tendency to leave machine maintenance to maintenance. This is due to lack of standard machine maintenance, lack of training for operators, operators are less skilled in carrying out maintenance, and also inadequate working environment. A common problem nowadays is the problem of porosity in the die casting part due to incorrect TPM during prevention and operators who do not understand the potential of preventive cooling cause porosity and prevention as it starts from cooling propagating to porosity to other abnormal parts.